2020
DOI: 10.1186/s13073-020-00778-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA copy number can influence mortality and cardiovascular disease via methylation of nuclear DNA CpGs

Abstract: Background Mitochondrial DNA copy number (mtDNA-CN) has been associated with a variety of aging-related diseases, including all-cause mortality. However, the mechanism by which mtDNA-CN influences disease is not currently understood. One such mechanism may be through regulation of nuclear gene expression via the modification of nuclear DNA (nDNA) methylation. Methods To investigate this hypothesis, we assessed the relationship betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 63 publications
4
60
1
Order By: Relevance
“…Recently, it was shown that mitochondrial DNA copy number (mtDNA-CN) was inversely associated with incident and prevalent cardiovascular disease outcomes in 21,870 participants from three independent cohorts [36] . Shortly after, in our laboratory, we found that mtDNA-CN was decreased in varicose vein vs. non-varicose vein tissue samples [37] . Then, Castellani et al [38] demonstrated across multiple independent cohorts that changes in mtDNA-CN influence nuclear DNA methylation at specific CpG loci and result in differential expression of specific genes that may impact human health and disease (namely, cardiovascular disease and all-cause mortality) via altered cell signaling [38] .…”
Section: Where Are We Now In Terms Of Learning In Terms Of Understanding and Where Are We Going? A Challenge For The Futurementioning
confidence: 86%
“…Recently, it was shown that mitochondrial DNA copy number (mtDNA-CN) was inversely associated with incident and prevalent cardiovascular disease outcomes in 21,870 participants from three independent cohorts [36] . Shortly after, in our laboratory, we found that mtDNA-CN was decreased in varicose vein vs. non-varicose vein tissue samples [37] . Then, Castellani et al [38] demonstrated across multiple independent cohorts that changes in mtDNA-CN influence nuclear DNA methylation at specific CpG loci and result in differential expression of specific genes that may impact human health and disease (namely, cardiovascular disease and all-cause mortality) via altered cell signaling [38] .…”
Section: Where Are We Now In Terms Of Learning In Terms Of Understanding and Where Are We Going? A Challenge For The Futurementioning
confidence: 86%
“…Moreover, mtDNA variants may have effects on the transcription of genes in the nuclear genome through epigenetic mechanisms, as the removal of mtDNA or changes in mtDNA haplogroups have been found to be associated with differences in nuclear DNA methylation levels [ 27 , 28 , 29 ], suggesting an important epigenetic interplay between the two genomes. Recently, it has also been observed that changes in the mtDNA copy number influence nuclear DNA methylation at specific loci and result in differential expression of specific genes that may impact human health and disease via altered cell signaling [ 30 ]. On the other hand, nuclear epigenetics modulates mitochondrial function, as many of the mitochondrial proteins are nuclear-encoded.…”
Section: Mitoepigeneticsmentioning
confidence: 99%
“…As shown in previous studies, the number of mtDNA copies in the peripheral blood decreases with age [ 38 ], and the decrease is negatively associated with age-related events, such as all-cause mortality [ 39 ]. In addition, mtDNA copy number loss is associated with cognitive function [ 40 ], cardiovascular diseases [ 41 ], and infectious morbidity and mortality in patients with chronic kidney disease [ 42 ]. Mitochondrial DNA depletion syndrome (MTDPS) refers to diseases in which the mtDNA copy number is reduced, and mitochondrial energy metabolism is impaired [ 43 ].…”
Section: Introductionmentioning
confidence: 99%